Testicular biopsy during orchidopexy procedure: Does it have an adverse effect on fertility? - KIYAN, GÜRSU (KARGER, 2005)
Introduction: The aim of this study is to evaluate the effect of the gonadal biopsy procedure on fertility and histology of the experimentally created undescended testis. Materials and Methods: Thirty Wistar- Albino rat litters were divided into three groups. In the first two groups, undescended testes were obtained by dividing the right gubernaculum in the first 48 h and the third group constituted the sham group. When the rats were 30 days old, orchidopexy was performed in the first group (O), whereas orchidopexy and testicular biopsy were performed in the second group (OB). After the fertility study all rats were sacrificed at week 11 and testicular weights, mean seminiferous tubular diameters (MSTD) and mean testicular biopsy scores ( MTBS) were measured. Results: One testis in the O group and three testes in the OB group were atrophied and these rats were excluded from the study. Testicular weights, MSTD and MTBS values of the operated side in the O and OB groups were lower than those in the sham group. There was a statistically significant cant difference between the MSTD values of the ipsilateral testes in the OB group and sham group ( p < 0.05). MTBS values of the ipsilateral testes in the O and OB groups were <8. There was no difference in all parameters in the contralateral testes between all groups (p > 0.05). All the evaluated rats were fertile. While there was no difference in number of fetuses and fertility scores between the O and OB group, however, the differences were significant between each of these groups and the sham group (p < 0.05) Conclusion: Testicular biopsy in the unilateral undescended testis model results in limited histological changes without affecting the fertility.
Keywords: cryptorchidism; testicular biopsy; fertility; UNILATERAL CRYPTORCHIDISM; TESTIS; RAT; BOYS; GUBERNACULUM; HISTOLOGY; SURGERY; DESCENT; COHORT; MODEL